Unearthing truths in duoethnographic method. (8th August 2016) - Farquhar, Sandy; Fitzpatrick, Esther
Abstract : Purpose: – The purpose of this paper is to engage with challenges the authors encountered in duoethnographic inquiry, including questions about what it means to tell the truth, and the decisions the authors made about what stories to include and exclude. The focus is on the ethical challenges involved in duoethnography and the ways in which the authors chose, and or felt compelled to, overcome them. The authors provide an argument for the need of intimate, eclectic and open-ended inquiry-based research that poses questions, challenges dominant discourses and promotes a compositional methodology in which to explore lived the experience of participants. Design/methodology/approach: – The authors' own duoethnographic process, embedded in an anthropological hermeneutics (Ricoeur, 1991), within a mode of narrative inquiry, developed over a period of three to four months. The authors had a number of formal and informal conversations – some recorded and transcribed, others remembered and reflected on later in e-mails or in draft academic papers. The authors shared articles, e-mailed, conversed with family and examined photos. Reflecting on some of these conversations, the authors were sometimes uncomfortable with the way the stories they shared had the potential to expose aspects of themselves and those the authors are close to. The authors developed fictionalising techniques and poetry in order to tell these stories. Findings: – Duoethnography engages with method that reveals truth as layered, contradictory and necessarily intersubjective. It is this tentative and contingent nature of truth that augers for a hyper-consciousness of the relationship between transgression and transformation. Using fictional ways of knowing: poetry, scripting and metaphor; and the usual technologies of research: anonymisation, de-identification; and drawing on notions of redaction and under erasure the authors found safe ways to represent particularly challenging issues. The process involved intimate revealing – small stories that the authors shared here to argue for the importance of the affective in transformative educational research. Research limitations/implications: – The authors continue to work in uncomfortable places and suggest that ethics often involves irreconcilable and incommensurate discourses which cannot always be accounted for in normalised codes of ethics. The authors argue that this tension provides an important on-going ethical encounter where, as researchers, the authors continue to generate and implement creative and innovative methodologies. Originality/value: – Throughout the paper the authors have suggested ways to challenge the linear, logical and the predictable as the authors wrestled with how personal narratives may reveal personal truth and transformation that may open ways for larger transformative actions.